Conservation Impact on Sacred forest Fragments - a Case Study from Karnataka, India - Ray, Rajasri; Subhas Chandran, M. D.; Ramachandra, T. V. (Indian Forester, 2012)
The impact of protection on the ecology and ecosystem services of a fragmented sacred grove of Karnataka in agricultural landscape was studied. Comparative assessment of two time scale data revealed positive influence of protection on vegetation in term of species richness, diversity, endemism and basal area. An increment in above ground biomass indicates groves potential for carbon sequestration. Species level study on carbon storage finds the contribution of young individuals in recent time period.